STRATEGI MARKETING BRAND DI NEW MEDIA - Murtani, Hanafi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2014)
The growth of the Internet as a new media (new media) is a very fast has changed the way companies do business changes, the way we communicate and interact with the audience. Internet revolution continues, increasing Internet audience. The Internet is an interactive communication medium that is an integral part of the communication strategy and even business strategy for many companies. The purpose of this research is to determine how the brand is able to adapt to changes, particularly the use of social media, and be able to be a medium of communication for the audience and superior to its competitors, with a case study conducted on social media The Body Shop Indonesia. This study uses a case study with a descriptive qualitative research, namely to understand social phenomena with an overview and in-depth understanding. The paradigm used in this study is the constructivist paradigm with data collection techniques through in-depth interviews and observations on the subject of research. The results showed that the implementation of brand marketing strategy in new media, particularly on social media was The Body Shop Indonesia has been able to attract visitors and consumers, despite the emergence of The Body Shop Indonesia is relatively new socially mediated.